Experimental Investigation of Hydraulic Fracturing in Vertical and Horizontal Perforated Boreholes - Fallahzadeh, Seyed Hassan; Rasouli, Vamegh; Sarmadivaleh, M. (ARMA, 2013)
In this study, scaled hydraulic fracturing tests are conducted on 10 and 15 cm cubical mortar samples. The importance of scaled fracturing tests should be highlighted as the results of non-field-like fracturing tests cannot be compared with or used for actual fracturing operation. Three independent principal stresses were applied to the samples using a True Tri-axial Stress Cell (TTSC). The hole and perforations were made into the sample after casting and curing were completed. Various scenarios of vertical and horizontal wells and in-situ stress regimes were modeled. These two factors play a significant role in fracture initiation and near wellbore propagation parameters; however they are not independent from each other and should be analyzed simultaneously. The results showed that when the least stress component is perpendicular to the axis of the perforations, less fracturing pressures would be required. It is also shown that, even when the cement sheath is failed, the orientation of the perforations affects the fracturing process noticeably. Furthermore, it was found that stress anisotropy influences the fracturing mechanism in a perforated borehole, and affects the geometry of the fracture close to the wellbore.